Impact of marginalization on tobacco use in individuals diagnosed with head and neck Cancer - Scott, Grace M; Best, Corliss; Fung, Kevin; Gupta, Michael; Sommer, Doron D; Szeto, Christopher; Micomonaco, Damian C (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Considerable evidence now indicates that individuals living in underprivileged neighbourhoods have higher rates of mortality and morbidity independent of individual-level characteristics. This study explored the impact of geographical marginalization on smoking cessation in a population of individuals with a diagnosis of head and neck cancer. The aims of this study were twofold: (1) assess the prevalence of smoking cessation in those with a previous diagnosis of head and neck cancer, (2) analyze the determinants of smoking alongside area-based measures of socioeconomic status. Methods This was a cross-sectional study. We administered a self-reported nicotine dependence package to participants between the ages of 20–90 with a previous mucosal head and neck cancer diagnosis and with a history of tobacco use. Using the Canadian Marginalization (CAN-Marg) Index tool based on 2006 Canada Census data we compared the degree of marginalization to the smoking status. For those individuals who were currently smoking, nicotine dependence and readiness to quit were assessed. A summative score of marginalization was compared to smoking status of individuals. Results The results from this study indicate that the summative level of marginalization developed from the combined factors of residential instability, material deprivation, ethnic concentration and dependency may be important factors in smoking cessation. Conclusions This analysis of determinants of smoking alongside area-based measures of socioeconomic status may implicate the need for targeted population-based smoking cessation interventions.